Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1287/mnsc.2014.2015
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Effects in Online Group Buying

Abstract: This paper studies two types of threshold-induced effects: a surge of new sign-ups around the time when the thresholds of group-buying deals are reached, and a stronger positive relation between the number of new sign-ups and the cumulative number of sign-ups before the thresholds are reached than afterwards. This empirical study uses a dataset that records the inter-temporal cumulative number of sign-ups for groupbuying deals in 86 city markets covered by Groupon, during a period of 71 days when Groupon predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 21 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…Kuppuswamy and Bayus (2013) use data to try and empirically understand the dynamics of crowdfunding, and find that the propensity of backers to contribute is influenced by how much has already been pledged. Similar effects are found by Wu et al (2014) in the context of group buying. This is consistent with the empirical and experimental literature on public goods.…”
Section: Related Literaturesupporting
confidence: 78%
“…Kuppuswamy and Bayus (2013) use data to try and empirically understand the dynamics of crowdfunding, and find that the propensity of backers to contribute is influenced by how much has already been pledged. Similar effects are found by Wu et al (2014) in the context of group buying. This is consistent with the empirical and experimental literature on public goods.…”
Section: Related Literaturesupporting
confidence: 78%
“…Chen and Roma (2011) show that, in contrast to the general convention, buyers who compete for consumers can suffer losses by adopting cooperative purchasing. Empirical studies are ample; see, for instance, Kauffman and Wang (2002), Wu, Shi, and Hu (2015), and henceforth. The prior literature mainly investigates group buying as a purchasing option that is initiated by vendors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical research has found supportive evidence to this strategy. Group buying or daily deal websites can facilitate product sales by displaying information on deal popularity or social influence (Li and Wu 2013;Luo et al 2014;Wu et al 2015).…”
Section: Related Literaturementioning
confidence: 99%